Pengaruh Metode Project Based Learning terhadap Kemampuan Bercerita untuk Anak Usia Dini di TK Cahaya Mentari Langkapura Bandar Lampung - Kurnia, Indri; Sugiyanto; Dewantari, Tri (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study evaluates the effectiveness of Project Based Learning (PjBL) in enhancing storytelling skills among early childhood students at TK Cahaya Mentari Langkapura, Bandar Lampung. PjBL, an instructional method centered around projects, aims to guide students in solving complex problems through real-life experiences and active exploration. The study involved pretest and posttest phases to assess the development of children's storytelling abilities before and after implementing PjBL. The results indicate that PjBL significantly improved storytelling interest and confidence, with 73% of children showing increased interest and bravery, 87% starting to present in front of the class, and 53% doing so effectively after PjBL. Additionally, 60% of children understood the importance of proper intonation, and 80% could correctly construct simple sentences. Statistical analysis with a p-value of .000 confirms that the observed improvements were not due to chance. These findings underscore that PjBL is effective in developing storytelling skills, creativity, and collaboration in early childhood education.